STUDY OF POTENTIAL FLOOD PRONE AREAS IN AIR RAMI MUKOMUKO DISTRICT - Suprina, Dewi; Juita, Erna; Farida, Farida (STKIP PGRI Sumbar, 2013)
The flood disaster is the interaction between man and nature caused by human adjustment systems in nature and capitalize upon the natural system itself. In this case the flood is an aspect of human interaction in the group should try natural useful and avoids harm to human nature it is done sendiri.Penelitian to see the potential of flooding that occurred in Water District Rami .This study classified as descriptive qualitative research . Descriptive research Qualitative research is a procedure that uses descriptive data in the form of words written or spoken of the people and actors that can be observed . the research focus on the actual problems that are or have happened and what the data is desired without being manipulated .Based on the study, the potential floding area accured at F1.1.Reg.Pr.QTb at Desa Rami , V1.2.Lat.Pm.QTb at Desa Talang Rio , and F1.1.Lat.Pr.QTb Desa Dusun Pulau at induded as zone III( high potential of flooding) Â . the flooding in Air Rami sub distret caused by rainflall, land use and water of river Debit.Â Key Word : rainfall, land use, streamflow, flood frequency, flooding residence time, and inundation depth.